![\frac{1 + cos \: a}{1 - cos \: a } = {(cos \: a \: + cot \: a \: ) }^{2} \frac{1 + cos \: a}{1 - cos \: a } = {(cos \: a \: + cot \: a \: ) }^{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1+%2B+cos+%5C%3A+a%7D%7B1+-+cos+%5C%3A+a+%7D++%3D++%7B%28cos+%5C%3A+a+%5C%3A++%2B+cot+%5C%3A+a+%5C%3A+%29++%7D%5E%7B2%7D+)
Answers
Answered by
1
Step-by-step explanation:
multiply lhs fraction numerator and denominator with (1+ cosA)
1+cosA (1+cosA)² 1+cos²A+2cosA
______ = _______ = ____________
1-cosA 1- cos²A sin²A
=1/sin²A +(cosA/sinA)² + 2*(cosA/sinA)(1/sinA)
= csc²A + cot²A + 2cotA cscA
=(cscA+cotA)²
Similar questions
Computer Science,
3 months ago
English,
3 months ago
Political Science,
6 months ago
Math,
6 months ago